Possibility to locate the position of the H2O snowline in protoplanetary disks through spectroscopic observations. Issue Volume 14:Issue S345(2019) (August 2018) - Notsu, Shota; Nomura, Hideko; Walsh, Catherine; Honda, Mitsuhiko; Hirota, Tomoya; Akiyama, Eiji; Tsukagoshi, Takashi; Booth, Alice S.; Millar, T. J.
Abstract: Observationally locating the position of the H2 O snowline in protoplanetary disks is crucial for understanding planetesimal and planet formation processes, and the origin of water on the Earth. In our studies, we conducted calculations of chemical reactions and water line profiles in protoplanetary disks, and identified that ortho/para-H2 16 O, H2 18 O lines with small Einstein A coefficients and relatively high upper state energies are dominated by emission from the hot midplane region inside the H2 O snowline. Therefore, through analyzing their line profiles the position of the H2 O snowline can be located. Moreover, because the number density of the H2 18 O is much smaller than that of H2 16 O, the H2 18 O lines can trace deeper into the disk and thus they are potentially better probes of the exact position of the H2 O snowline in disk midplane.